2018
DOI: 10.3390/genes9030130
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Transcriptome Assembly and Characterization of the Synthesis Genes of Bioactive Constituents in Abelmoschus esculentus (L.) Moench

Abstract: Abelmoschus esculentus (okra or lady’s fingers) is a vegetable with high nutritional value, as well as having certain medicinal effects. It is widely used as food, in the food industry, and in herbal medicinal products, but also as an ornamental, in animal feed, and in other commercial sectors. Okra is rich in bioactive compounds, such as flavonoids, polysaccharides, polyphenols, caffeine, and pectin. In the present study, the concentrations of total flavonoids and polysaccharides in five organs of okra were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 54 publications
0
13
1
Order By: Relevance
“…The comparative transcriptome analysis showed that the number and N50 sizes of the assembled unigenes from the present A. esculentus leaf transcriptome were larger than the previous reported transcriptome from Schafleitner, et al However, very recently Zhang, et al [52] reported A. esculentus transcriptome from root, stem, leaves, flowers, and fruits with 293,971 unigenes having N50 sizes of 1885 bp, which was better than our leaf transcriptome. The present, reported transcriptome assemblies along with precursors miRNA sequencing data [12] from A. esculentus can be merged to obtain comprehensive sequence information of this crop plant which will be useful for the functional genomics, host-pathogen interaction, and mRNA-miRNA network studies.…”
Section: Identification Of Simple Sequence Repeats (Ssrs) Of a Esculcontrasting
confidence: 76%
“…The comparative transcriptome analysis showed that the number and N50 sizes of the assembled unigenes from the present A. esculentus leaf transcriptome were larger than the previous reported transcriptome from Schafleitner, et al However, very recently Zhang, et al [52] reported A. esculentus transcriptome from root, stem, leaves, flowers, and fruits with 293,971 unigenes having N50 sizes of 1885 bp, which was better than our leaf transcriptome. The present, reported transcriptome assemblies along with precursors miRNA sequencing data [12] from A. esculentus can be merged to obtain comprehensive sequence information of this crop plant which will be useful for the functional genomics, host-pathogen interaction, and mRNA-miRNA network studies.…”
Section: Identification Of Simple Sequence Repeats (Ssrs) Of a Esculcontrasting
confidence: 76%
“…Previous work focused on identification and analysis glycosyltransferases (GTs) in polysaccharides biosynthesis 20 . Besides GTs, some metabolic pathways such as fructose and mannose metabolism may also participated in polysaccharides biosynthesis 21,22 . However, the biosynthesis mechanisms and metabolic pathways of polysaccharides have been not explored detailly in D. huoshanense.In China, the stem of Dendrobium is a traditional edible and medicinal part 2 .…”
mentioning
confidence: 99%
“…Okra is now widely cultivated all over the world [30]. Due to the complex allopolyploid genome of okra (probably, 2n = 130–140), little attention has been paid to the genetic improvement of this crop until recently [31]. In the present work, a TMT-based proteomic technique was employed to analyze the proteins differentially expressed between the control and NaCl-treated seedlings over the first 48 h. These results will enhance our understanding of the regulatory mechanisms involved in okra response to salt stress.…”
Section: Discussionmentioning
confidence: 99%